Soil and water conservation practices among the independent's oil palm smallholders at the Saratok's cooperative - Mohamad Arfan, Johari (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Knowledge on implementation of soil and water conservation practices (SWCP) are importance to be adopted by oil palm growers in order to maintain the quality of natural resources and also committed with the environmental conservation. As one ofthe criteria in the Malaysian Palm Oil Board Good Agricultural Practices (MPOB-GAP), it must be adopted in order to qualify the oil palm growers, especially smallholders to be certified with the quality certifications as well as to increase FFB yields and incomes. The Malaysian government through relevant agency has made an effort to group the independent oil palm smallholders through cooperative under the Sustainabletalm Oil Clusters (SPOC) to facilitate the extension activities and certification programs. This study was carried out in Saratok District under Betong Division involving the mem ers of Saratok's Sustainable Oil Palm Growers Cooperative (KPSMDS). The objective of this study is to evaluate the knowledge and current adoption of SWCP in the smallholder farms. In this study, conservation practices implemented by oil palm smallholders were evaluated based on the checklist in the Roundtable on Sustainable Palm Oil (RSPO) principle number four, criteria 4.2, 4.3 and 4.4. Research methods that have been used in this study are in-situ observation and face to face interview session with KP DSMS participants. The results of the study indicated that the implementations of soil and water conservation practices were still low implemented by the oil palm smallholders. The knowledge regarding the good agricultural practices is the main factor that influences the status of implementation of both soil and water conservation practices. Recommendations based on the research affirm that it is necessary to take into account the education program for the cooperative's members in order 10 ensure that their awareness of the practices is high and adoption of sWCP were implemented for the independent's smallholders benefit.